Innovations in Biomedical Engineering - Gzik, Marek; Tkacz, Ewaryst; Paszenda, Zbigniew; Piętka, Ewa (Advances in Intelligent Systems and Computing,, 2017)
This book presents the proceedings of the "Innovations in Biomedical Engineering IBE'2016" Conference held on October 16-18, 2016 in Poland, discussing recent research on innovations in biomedical engineering. The past decade has seen the dynamic development of more and more sophisticated technologies, including biotechnologies, and more general technologies applied in the area of life sciences. As such the book covers the broadest possible spectrum of subjects related to biomedical engineering innovations. Divided into four parts, it presents state-of-the-art achievements in: • engineering of biomaterials, • modelling and simulations in biomechanics, • informatics in medicine • signal analysis The book helps bridge the gap between technological and methodological engineering achievements on the one hand and clinical requirements in the three major areas diagnosis, therapy and rehabilitation on the other. .